Theories and Experiments of Torpedo Shaped Charge Warhead Penetration into Water-partitioned Armor - Qifeng ZHU; Qin LI; Tuanmeng WANG; Wei SHANG; Hongbing MA (水下无人系统学报)
To reasonably predict the penetration power of a torpedo shaped charge warhead into water-partitioned armor, a theoretical model for calculating the generated penetration depth and aperture diameters was proposed based on the A-T model and the two-step mechanism of aperture growth in combination with the penetrator penetration process analysis based on the virtual origin theory. The experiments and simulations for a reduced-scale torpedo shaped charge warhead penetration into water-partitioned armor targets were conducted, in which a single-layer aluminum plate and the spaced aluminum plates with a certain cumulative thickness were used to simulate the torpedo heads. Calculations, simulations, and experimental results were then compared and analyzed, which verified the rationality of the theoretical model. The research can provide support for the penetration power prediction and the optimization design of torpedo shaped charge warheads, as well as the technical research of new powerful torpedo shaped charge warheads to more effectively destroy the submarine protective structure.